2010
DOI: 10.1108/00070701011074363
|View full text |Cite
|
Sign up to set email alerts
|

Consumer food safety education for the domestic environment: a systematic review

Abstract: PurposeDespite the recognised importance of food-safety, a large number of consumers do not practice adequate food-safety in the home. Many studies have recommended that education is a key step in preventing food borne illness in the domestic environment. However, few educational or psychosocial interventions have been designed and implemented to improve food-safety knowledge, attitudes and behaviours. Even fewer of these studies have been subject to rigorous appraisal. A systematic review of studies that desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 45 publications
2
48
0
1
Order By: Relevance
“…Overall, the results of the present study add further evidence to suggest that the TPB is a useful framework for food safety and address the many calls in the literature that have been campaigning for such theoretical underpinnings (Griffith et al, 1995;Milton & Mullan, 2010).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Overall, the results of the present study add further evidence to suggest that the TPB is a useful framework for food safety and address the many calls in the literature that have been campaigning for such theoretical underpinnings (Griffith et al, 1995;Milton & Mullan, 2010).…”
Section: Discussionsupporting
confidence: 70%
“…Calls have been made in the literature for food safety interventions to have a greater theoretical foundation through the use of social cognition models (SCM; Griffith, Mullan, & Price, 1995;Milton & Mullan, 2010). A recent systematic review found that only 10 published studies examining psychosocial food safety interventions had occurred in the developed world (Milton & Mullan, 2010).…”
mentioning
confidence: 99%
“…However, an insight into what consumers know and what they need to be educated about can be obtained by such reported behavior . If preventive measures and proper food handling and preparation practices are applied, most foodborne diseases cases can be prevented (Azevedo, Albano, Silva, & Teixeira, 2014;Milton & Mullan, 2010;Powell, Jacob, & Chapman, 2011). However, as farm produce and food products are not pathogen-free, whoever handles and prepares food at home plays an essential role in preventing such diseases (Medeiros, Hillers, Kendall, & Mason, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of food safety interventions (Milton & Mullan, 2010) found that they have been predominantly educational, using persuasive messages and targeting knowledge, for example the ‗Fight Bac' intervention (www.fightbac.org, 2002) and ‗Now You're Cooking... using a Food Thermometer' (Takeuchi, Hillers, Edwards, Edlefsen, & McCurdy, 2005). The Fight Bac intervention was successful at increasing knowledge of food hygiene compared to non-exposed counterparts, however it only increased actual behaviours, such as defrosting meat in the refrigerator, by approximately 7% (Dharod, Pérez-Escamilla, Bermúdez-Millán, Segura-Pérez, & Damio, 2004).…”
mentioning
confidence: 99%